Safety Performance Index Industri Batik Tulis Berdasarkan Kriteria Majemuk - Nachnul Ansori; Trisita Novianti; Fitri Agustina; Nur Rakhmawati (Institute of Research and Community Outreach - Petra Christian University, 2015)
Accident generally occurs due to the activities which is done in unsafe conditions or even unsafe behavior. These conditions can influence workers productivity. In batik industries, those workers use toxic material and work in non ergonomic atmosphere. Moreover, they also do not take care of the environment and do not use personal protective equipments (PPE). Workers at Madura batik SMEs have not fully realized the significance of occupational health and safety (OHS) in their working areas. The aims of this research is to evaluate OHS performance based on the indicators of safety performance index (SPI), which is multicriteria, in that industri. The safety performance attributes were obtained from factor analysis from the previous study. The index is calculated based on the weighted evaluation results of critical behavior checklist (CBC), integrated with analytical hierarchy process (AHP). As the results, we should give priority to improve the knowledge and experience toward OHS of the workers and also improve the working environment of the Madura’s batik industries. Additionally, the performance of OHS in coloring process is also on the threshold of unsafe condition, further development on the coloring process is needed.